Book Review: Wells, Gordon. (Ed.). (2001). Action, talk, and text: learning and teaching through inquiry. New York: Teachers College, Columbia University. - Mary Hookey (Networks: An Online Journal for Teacher Research, 2003)
In 1990, Marilyn Cochrane-Smith and Susan Lytle argued that "What is missing from the knowledge base for teaching are the voices of the teachers themselves, the questions teachers ask, the ways teachers use writing and intentional talk in their work lives, and the interpretive frames teachers use to understand and improve their own classroom practices." The ultimate goal for teachers is the enhanced learning of their students.